If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + -3x = -4x Solving 7 + -3x = -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. 7 + -3x + 4x = -4x + 4x Combine like terms: -3x + 4x = 1x 7 + 1x = -4x + 4x Combine like terms: -4x + 4x = 0 7 + 1x = 0 Add '-7' to each side of the equation. 7 + -7 + 1x = 0 + -7 Combine like terms: 7 + -7 = 0 0 + 1x = 0 + -7 1x = 0 + -7 Combine like terms: 0 + -7 = -7 1x = -7 Divide each side by '1'. x = -7 Simplifying x = -7
| 5x+12=4/8 | | 1/5(2X-6)=3 | | -88+7x=-85-9x | | y=36-3x^2-2x^3 | | -4/5x+2/25x+1/15x | | 4(6c-6)= | | p^2-p-1=0 | | 9/2=8*1/8 | | 137-2x=5x+11 | | 10x^2+17x-42=0 | | 4(tan)x=1 | | a(a-17)=(-60) | | 8n-118= | | y=1/2+2 | | 0.5X+6=0.4x | | 5x+2=6/7 | | 4tanx=1 | | y=0/2+2 | | 3x+12=7/3 | | 10x^2+7x-42=0 | | 21=5x/6+3x/2 | | 25/2/5/12 | | 8x^2-3x+7=0 | | 4000/300000 | | 8x+6=5/6 | | y=-1/2+2 | | 5x-5=10/4 | | a(a+17)=(-60) | | 8+4z-5=8z+13-2z | | 2w^2-4w-20=0 | | -24-6x=11-10x | | 2x^2+20-7x=0 |